1998
DOI: 10.1002/pro.5560070907
|View full text |Cite
|
Sign up to set email alerts
|

Uclacyanins, stellacyanins, and plantacyanins are distinct subfamilies of phytocyanins: Plant‐specific mononuclear blue copper proteins

Abstract: The cDNAs encoding plantacyanin from spinach were isolated and characterized. In addition, four new cDNA sequences from Arubidopsis ESTs were identified that encode polypeptides resembling phytocyanins, plant-specific proteins constituting a distinct family of mononuclear blue copper proteins. One of them encodes plantacyanin from Arubidopsis. while three others, designated as uclacyanin 1, 2, and 3, encode protein precursors that are closely related to precursors of stellacyanins and a blue copper protein fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
169
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(173 citation statements)
references
References 79 publications
4
169
0
Order By: Relevance
“…A validated target for ptr-miR408, a plastocyanin-like protein, is interesting because this class of proteins is believed to mediate lignin polymerization (Nersissian et al, 1998). The near absence of ptr-miR408 transcripts in developing xylem, the major lignification tissue, and the moderate expression of ptr-miR408 in low lignin containing tissues, phloem and leaf (Figure 2), support the role of ptr-miR408 in coordinating lignin deposition in different tissues.…”
Section: Targets Were Experimentally Validated For Nonconserved Ptr-mmentioning
confidence: 89%
“…A validated target for ptr-miR408, a plastocyanin-like protein, is interesting because this class of proteins is believed to mediate lignin polymerization (Nersissian et al, 1998). The near absence of ptr-miR408 transcripts in developing xylem, the major lignification tissue, and the moderate expression of ptr-miR408 in low lignin containing tissues, phloem and leaf (Figure 2), support the role of ptr-miR408 in coordinating lignin deposition in different tissues.…”
Section: Targets Were Experimentally Validated For Nonconserved Ptr-mmentioning
confidence: 89%
“…These include TCs that encode proteins similar to: (a) purine permease, a high-affinity transporter for adenine, cytosine, and purine derivatives (Gillissen et al, 2000); (b) plantacyanin, a plant-specific blue copper protein, apparently involved in the defense response (Nersissian et al, 1998); (c) a homolog of an Arabidopsis embryospecific protein, whose cellular function is yet to be understood; (d) B12D protein, a protein known to be accumulated in plants during embryo development, seed maturation, and leaf senescence (Aalen et al, 1994;Huang et al, 2001); (e) remorin, a membrane phosphoprotein, suggested to be involved in intercellular communications (Reymond et al, 1996); (f) 2-on-2 hemoglobin, the higher plant homolog of the "truncated" hemoglobins found in bacteria, protozoa, and algae, which possess unique biochemical properties that are likely distinct from those of other plant hemoglobins (Watts et al, 2001); and (g) calmodulinlike proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The nucleotide sequence of TC32101 is 97% identical to that of nodulin MsNod202 encoding a plantacyanin from M. sativa . Together with two other nodulins, ENOD16 and ENOD20 (Greene et al, 1998), corresponding to nodule-specific TC40417 and TC28429, these proteins contain a copper-binding domain characteristic of a group of plant phytocyanins proposed to be involved in primary defense response (Nersissian et al, 1998). Another copper-related nodule-specific TC appears to encode a putative copper transporter (TC37150).…”
Section: Characterization Of Nodule-specific Tcsmentioning
confidence: 99%
“…Redox reactions play many roles in plant cell walls during development as well as in response to pathogen attacks [54][55][56][57]. In addition to peroxidases, several CWP might be involved in such processes.…”
Section: Towards New Biological Functions In Cell Wallsmentioning
confidence: 99%